Coping strategies among emotionally abused students in Batam : a case study - Nuraya (Kulliyyah of Education, International Islamic University Malaysia, 2020)
Emotional abuse is a maltreatment, which results in impaired psychological growth and development. Although emotional abuse does not leave physical scars, it can still bring huge impact on children's confidence and self-esteem. Less attention that the have been given to the effects of children's emotional and psychological abuse. However, it is worrying if the children have negative thinking about their life due to being emotional abused. The purpose of this study is to identify experiences, causes, and effects of emotional abuse and to investigate the coping strategies among emotionally abused students. This study employed a qualitative research design and the target respondents were three female students. A purposive sampling has used to select the participants through a counselor and they all participated voluntarily. Semi-structured interviews and observations have used to collect the data. A framework on the development of coping has presented. Findings indicated that family background was the major factor that contributes to the emotional abuse of these students. The participants have developed their own coping strategies through their age-graded shifts as an episodic process and in how they detected and responded to the actual problems in their everyday life. Basic religion is used to develop their confidence to making in decisions for their future. These findings are important as they contribute to our understanding on the adverse effects of emotional abuse on later childhood development.